PRESIDEN JOKO WIDODO: POTRET TINDAK TUTUR PENANGANAN MASALAH SOSIAL-POLITIK BANGSA - Burhanuddin, Burhanuddin; Sumarlam, Sumarlam (Sunan Kalijaga State Islamic University Yogyakarta, 2015)
This research intends to elaborate the types and domains of President Joko Widodo’s speaking politeness strategies in addressing the nation’s socio-political issues. The simplified Brown and Levinson’s (1987) speaking politeness strategies have been employed to achieve the intended purpose of this investigation. The data was collected through listening method and the extra-lingual equivalent method was employed to analyze the data (Sudaryanto, 1993; Mahsun, 2005). Among the eleven speaking politeness strategies proposed by Brown and Levinson (1987), never has President Joko Widodo employed a joke strategy. It might be because the strategy is thought inappropriate with the topic delivered and is considered as a threat for national socio-political stability. The avoid disagreement strategy and the promise-offer strategy are the most often used strategies by President Joko Widodo, sharing 20% of each; followed by the in-group identitiy markers strategy and the intensify interest-seek agreement strategy, sharing 12% of each; the strategy of notice; attend to interest-wants (2%), and the four remaining strategies which counted for 7% each. The speech acts performed by President Joko Widodo contain some politeness strategies with considerable perlucosion power. However, the dominant use of certain strategies is mainly caused by the socio-cultural inferences, which influence the speaker to perform speech acts, rather than the speaker’s awareness and consciousness for selecting those strategies. The knowledge of dominant strategies of speaking politeness practiced by President Joko Widodo can be used as a base for understanding the pattern of the president’s characteristics to deal with the nation’s social and political issues.